PENGEMBANGAN MEDIA SEX KIDS EDUCATION (SKIDU) BERBASIS BOARD GAME UNTUK ANAK USIA DINI - Dewi Rahayu; Indryani Indryani; Bunga Ayu Wulandari (Jurnal Muara Pendidikan, 2023)
Sexual violence in early childhood has become increasingly common in recent years, making it sad for parents, educators and education practitioners, because this will definitely have negative impact on the child's future. The purpose of this study was to develop increasing Board Game-based Sex Kids Education (SKIDU) media for knowledge of sex education in early childhood. The subjects in this study were children aged 4-6 years at TK-IT Al Azka, Jambi City. The research method used is Research and Development (R&D). This development research procedure refers to the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). Validation of the feasibility of the SKIDU Board Game was carried out by material experts and media experts, and implemented to 16 B1 class students at TK IT Al-Azka Jambi. The results showed that the feasibility test of the SKIDU Board Game for Early Childhood obtained the results of validation by material experts at 98.00% with the very feasible category and the results of the validation by media experts obtained a value of 89.00% with the very feasible category. Then the parents' responses to the SKIDU Board Game product for Early Childhood obtained a value of 98.00% in the very feasible category, the educator's response obtained a value of 100% with a very positive category. Then based on one-to-one trials a value of 89.75% was obtained in the very high category, small group trials obtained a value of 85.50% in the very high category, and field trials obtained a value of 91.25% with a very high category. So that the Board Game-based Sex Kids Education (SKIDU) media is suitable for use by students as a instructional media.